Morbidity of Late-preterm Infants at Chaoprayayommaraj Hospital - Naka, Chonlathit (Journal of Health Science of Thailand, 2017)
The prospective cohort study was aimed at comparing the morbidity and rehospitalization between late-preterm and term infants, and to determine maternal factors of late-preterm infants. The study population were infants born in Chaoprayayommaraj hospital from Oct 1, 2011 to Dec 31, 2011 excluding infants with anormaly, twins and death before the end of the study. The primary outcome was morbidity in late-preterm infants comparing with term infants. The secondary outcome was rehospitalization. Statistical analysis was performed by using relative risk and 95% confidence interval for significant differences in morbidity, rehospitalization and maternal factors between late-preterm and term infants. Length of hospital stay of each group were established by t -test with statistical significance at p < 0.05. A total of 804 infants were enrolled, 57 infants in latepreterm group and 747 infants in term group. Late-preterm infants had a significantly higher incidence of morbidity: respiratory distress syndrome 11.8 (7.6, 18.4), hypoglycemia 11.1 (5.2,23.6), neonatal jaundice 2.9 (2.2,3.9), temperature instability 52.4 (11.4,241.1), sepsis 8 (4.9,13.2), poor feeding 15.3 (5.3,44) and had a significantly longer duration of hospital stay. Late-preterm infants were more likely to be hospitalized than term infants. Maternal factors that were more common in the late-preterm infants included chorioamnionitis, premature rupture of membrane, hypertension and teenage pregnancy.